Study on the Factors Influencing on Wetting Performance of Blasting Dust in a Limestone Mine - Jinrui Nie; Shujie Yuan; Ye Li; Xiaoming Huang (Geofluids)
In order to find out the factors influencing on wetting performance of blasting dust in open-pit limestone mines, the blasting dusts in a limestone mine in Tongling, Anhui Province, were studied. The samples of hydrophobic dust (MD) and hydrophilic dust (ND) were obtained by hydrostatic separation experiment. The contact angle of water on dust samples, particle size distribution, surface oxygen-containing functional groups, surface mineral composition and content, and surface pore structure was determined. The measurement results of contact angle indicate that the wetting performance of MD is weaker than that of ND. By comparative analyzing, the surface characteristics of MD and ND factors influencing on the wetting performance of the dusts were determined. The results showed that MD has a smaller particle size, higher volume fraction of hydrophobic groups, and more complex surface morphology than that of ND, which leads to its weaker wetting performance than that of ND.